2012
DOI: 10.1016/j.breast.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors gene polymorphisms may confer increased susceptibility to breast cancer development

Abstract: Toll-like receptor (TLR) activation may be an important event in tumor cell immune evasion. TLR2 and TLR4 gene polymorphisms have been related to increased susceptibility to cancer development in various organs. 261 patients and 480 health individuals were investigated for genotype and allelic frequencies of a 22-bp nucleotide deletion (-196 to -174del) in the promoter of TLR2 gene as well as two polymorphisms causing amino acid substitutions (Asp299Gly and Thr399Ile) in TLR4 gene. As far as (-196 to -174del) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 29 publications
2
32
0
2
Order By: Relevance
“…Moreover, recent epidemiological studies on different ethnic groups have indicated that TLR2Δ22 (-196-174 del) polymorphisms in toll-like receptor (TLR) family, significantly increases the risk of cervical, gastric, breast and hepatocellular cancers [15,24,25] but not in case of bladder, prostate and gallbladder cancers [16,26,27]. One recent study conducted on 261 BC patients and 480 healthy individuals has shown that genotype and allelic frequencies of a 22-bp nucleotide deletion (-196-174 del) in the promoter of TLR2 gene is significantly associated with increased risk of BC [24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent epidemiological studies on different ethnic groups have indicated that TLR2Δ22 (-196-174 del) polymorphisms in toll-like receptor (TLR) family, significantly increases the risk of cervical, gastric, breast and hepatocellular cancers [15,24,25] but not in case of bladder, prostate and gallbladder cancers [16,26,27]. One recent study conducted on 261 BC patients and 480 healthy individuals has shown that genotype and allelic frequencies of a 22-bp nucleotide deletion (-196-174 del) in the promoter of TLR2 gene is significantly associated with increased risk of BC [24].…”
Section: Introductionmentioning
confidence: 99%
“…There were many studies reported the association between Delta22 polymorphism and cancer risk and we also performed a meta-analysis on Delta22 inspired by the meta-analysis in Neoplasma. However, we found a significant publication bias by Begg's funnel plots and sensitivity analysis suggested that the study by Theodoropoulos et al (2012) significantly affect the pooled results (data not shown). In addition, for the +1350C>T polymorphism (rs3804100), we excluded a study of acute lymphoblastic leukemia (ALL), and added another one of thyroid cancer (Kim et DOI:http://dx.doi.org/10.7314/APJCP.2013.14.10.5871 Lack of Association of TLR2+597T>C, +1350C>T and Arg753Gln with Cancer Risk: A Meta-analysis al., 2012.…”
Section: Discussionmentioning
confidence: 76%
“…In agreement with these findings, Etokebe et al (34) failed to demonstrate any correlation between the TLR2 d allele and breast cancer development. However, a study by Theodoropoulos et al (35) reported a positive association between this polymorphism and an increased risk of breast cancer in the Greek population. The reason for this discordance may be attributed to different genetic backgrounds between the studied populations, varying sample sizes and heterogeneity of the tumors examined (36).…”
Section: Discussionmentioning
confidence: 95%